Lo straniero interiore. Il religioso come esperienza di alterità tra modernità e secolarizzazione - Celada Ballanti, Roberto (Bollettino Filosofico, 2019)
Moving from the idea of religiosity as a transcendental structure of consciousness, the essay aims to document the thesis that religiosity itself shows itself, especially in the time of Modernity, as an experience of radical alterity and eccentricity: otherness that precedes, exceeds, bypasses the man, without ever being able to completely come to terms with it, and without the historical religions themselves being able to fully master their origin. Keywords: Experience, Religion, Pluralism, Otherness, Transcendental